Zij al-Jadid ibn Asy-Syatir: Melacak Algoritma Awal Bulan Kamariah - Fika Afhamul Fuscha; Ahmad Izzuddin (Universitas Islam Negeri Mataram, 2023)
Zij al-Jadid ibn Asy-Syatir is a collection of astronomical tables that appeared before Zij al-Jadid ibn Asy-Syatir Ulugh Beg by applying the heliocentric theory paradigm. The theory is Ptolemy's geocentric theoretical model. Ibn Asy-Syatir was able to come out with a new heliocentric hypothesis and break the theory presented by Ptolemy, namely geocentric. Ibn Asy-Syatir utilizes this theory as a basis for producing Zij al-Jadid ibn Asy-Syatir. The purpose of this research is to analyze the method for the beginning of the lunar month Zij al-Jadid ibn Asy-Syatir which in Zij This has accepted the heliocentric hypothesis. This is significant to study since it differs from the understanding of the theory of the movement of celestial bodies Zij Sultani Ulugh Beg which arose later, but is nevertheless founded on the assumptions of Ptolemy's Geocentric theory. This study employs the method of library research with a descriptive approach. The findings of this study suggest that the first determination of the lunar month Zij al-Jadid ibn Asy-Syatir using the reckoning method haqiqi bi at-taqrib. In addition, the uniqueness of Zij is the zero point measurement of Tul al-Balad/Longitude of Place is 60° as measured from Sahil al-Bahr min Jihah al-Garb.